Modeling multi-generational diffusion for competitive brands: an analysis for telecommunication industries. Issue 4 (2nd October 2021) - Bansal, Gunjan; Anand, Adarsh; Aggrawal, Deepti
Abstract : Manufacturers keep bringing necessary rectifications in the products to achieve constant market penetration and high customer satisfaction. The present paper proposes a modeling framework wherein the impact of customer satisfaction with the first generation of a product is measured and its significant role has been incorporated in the adoption of a subsequent generation of the product. The model also integrates the influence of competition which is classified under two categories such that: - (a) competition within successive generations of the brand; and (b) competition among different brands. Further, model validation is performed using telecommunication industry sales data and sales are forecasted in two different ways i.e. using secondary data (a formal way) and primary data; where a survey of first-generation consumers is carried out and the concept of brand switching analysis and logistic regression have applied to analyze the market switching behavior and the satisfaction measure in the proposed models.